Tuberculosis Management in Renal Transplant Recipient - Tantular, Rezki (Universitaas Brawijaya, 2019)
Background: Tuberculosis (TB) is a major global health problem and South-East Asia was the leading contributor of TB cases globally. Treatment regimen of TB for an individual patient depends on multiple factors, and one of them was patient’s comorbidities. Comorbidities such as renal failure or concurrent use of immunosuppressant drugs post renal transplantation will influence pharmacological aspect of anti-tuberculosis drugs.Case: A 38-year-old male with a history of chronic renal failure who had undergone routine hemodialysis was diagnosed with pulmonary tuberculosis and was scheduled for a renal transplantation procedure. During the administration of anti-tuberculosis drugs in this patient, the physician mustconsider the kidney function, and possible drug interactions between anti-tuberculosis drugs especially rifampicin with immunosuppressant drugs used after renal transplantation. The initialregimen used in this patient was RHE which was followed by RH, but after using immunosuppressant drugs, rifampicin was replaced with moxifloxacin to avoid suboptimal effect of immunosuppressant drugs to prevent donor rejection, which is the biggest contributor ofmortality in transplant recipients in the first year post-transplantation.